CONTRIBUIÇÃO DA CRONONUTRIÇÃO NA PREVENÇÃO E TRATAMENTO DE DOENÇAS CARDIOVASCULARES – REVISÃO DE LITERATURA (REMUNOM, 2024)
The circadian system plays a crucial role in human health, regulating biological rhythms and directly influencing metabolism. Imbalances in this system can result in consequences such as eating disorders, weight gain, insulin resistance and increased risk of chronic diseases, including cardiovascular disease. Chrononutrition emerges as a promising therapeutic strategy when investigating the relationship between eating patterns, circadian rhythm and metabolic health. This study aimed to examine how aligning eating habits with the circadian cycle can  and treat metabolic imbalances, with a special focus on preventing cardiovascular disease. Through a literature review, scientific evidence was analyzed that indicates that chrononutrition, by synchronizing food intake with biological rhythms, can reduce risk factors such as obesity and hypertension. Furthermore, the final considerations of this article highlight the importance of nutritional education and preventive practices, such as adopting diets aligned with the circadian rhythm and regular physical activity, to reduce morbidity and mortality associated with cardiovascular diseases. Chrononutrition, therefore, presents itself as an effective therapeutic intervention in promoting cardiovascular health and improving quality of life.